Rural Development in Community Empowerment Through the Governance of Village-Owned Enterprises (BUMDES) - Sofyan Hadi; Auradian Marta; Raja Muhammad Amin; Rury Febrina (Nakhoda: Jurnal Ilmu Pemerintahan)
Sustainable national development is an important part of rural development that plays a role in empowering rural communities. In an effort to build Indonesia from villages, among others, village-owned enterprises are needed, which are supported by the legislation of Law Number 6 of 2014 concerning villages. It is hoped that BUMDes will be in favor of the community through the provision of socio-economic services. Meanwhile, BUMDes aims to seek profits by offering goods and services to the market. The existence of BUMDes is expected to increase the economic potential of the community through the principles of BUMDes governance. The principles of BUMDes governance are being cooperative, participatory, emancipatory, transparent, accountable, and sustainable. The objectives of this study are (1) to explore rural development in community empowerment through the governance of Village-Owned Enterprises in Mandau District, Bengkalis Regency. (2) To explain the factors that support and hinder rural development in the governance of Village-Owned Enterprises in Mandau District, Bengkalis Regency. The principle of Bumdes management in Mandau District, Bengkalis Regency, shows that cooperatively it has not been optimal in carrying out good cooperation in business development; participatorily, not all components seen in Bumdes have voluntarily provided support and contributed to the progress of BUMDes business; emancipatively, it can be seen that BUMDes managers lack female management members; in terms of transparency, there is still a lack of information disclosure and reporting submitted. Accountably, it is assessed that the resource capacity of BUMDes managers, lack of understanding of the role and vision and mission of BUMDes, in a sustainable way, has not been oriented towards the sustainability of BUMDes institutions and businesses. The factors supporting the principle of BUMDes management in Mandau District, Bengkalis Regency in poverty alleviation and village empowerment through BUMDes are very high. with an injection of BUMDes funds from villages, the Regency Budget, the Provincial Budget, and related ministries. Meanwhile, the inhibiting factors are the slow return of the budget lent to the community and the lack of functioning facilities made to bring profits to BUMDes businesses, such as market rentals and pertashops that are less profitable.